Toxic charity : how churches and charities hurt those they help (and how to reverse it) - Lupton, Robert D. (New York, NY : HarperOne, 2011)
Public service is a way of life for Americans; giving is a part of our national character. But compassionate instincts and generous spirits aren't enough, says veteran urban activist Robert D. Lupton. In this groundbreaking guide, he reveals the disturbing truth about charity: all too much of it has become toxic, devastating to the very people it's meant to help. In his four decades of urban ministry, Lupton has experienced firsthand how our good intentions can have unintended, dire consequences. Our free food and clothing distribution encourages ever-growing handout lines, diminishing the dignity of the poor while increasing their dependency. We converge on inner-city neighborhoods to plant flowers and pick up trash, battering the pride of residents who have the capacity (and responsibility) to beautify their own environment. We fly off on mission trips to poverty-stricken villages, hearts full of pity and suitcases bulging with giveaways--trips that one Nicaraguan leader describes as effective only in "turning my people into beggars." In Toxic Charity, Lupton urges individuals, churches, and organizations to step away from these spontaneous, often destructive acts of compassion toward thoughtful paths to community development. He delivers proven strategies for moving from toxic charity to transformative charity. Proposing a powerful "Oath for Compassionate Service" and spotlighting real-life examples of people serving not just with their hearts but with proven strategies and tested tactics, Lupton offers all the tools and inspiration we need to develop healthy, community-driven programs that produce deep, measurable, and lasting change. Everyone who volunteers or donates to charity needs to wrestle with this book.
Keywords: Community development -- Religious aspects; Charity -- Ethics -- Religion; Social service -- Religious aspects